2010
DOI: 10.1007/s00414-010-0421-0
|View full text |Cite
|
Sign up to set email alerts
|

Petechial bleedings in sudden infant death

Abstract: The autopsy reports of 484 cases of deceased infants (201 females, 283 males) were analysed retrospectively for the existence of external and internal petechial bleedings (PET). The cases were divided into five groups on the basis of the cause of death (sudden infant death syndrome, sepsis, airway infections, asphyxia and trauma). Internal PET (pleural, pericardial, epicardial, thymic and peritoneal) were observed in each group with a lower prevalence in cases of trauma. The highest prevalence of external (cut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…In forensic medicine literature, there exist numerous case descriptions of homicides that remained undetected during the external post-mortem examination but were finally revealed in the course of a subsequent autopsy [1,2,5,8,12,16]. Scientific investigations have shown that in Germany at least half of the homicides remain unrevealed.…”
Section: Discussionmentioning
confidence: 94%
“…In forensic medicine literature, there exist numerous case descriptions of homicides that remained undetected during the external post-mortem examination but were finally revealed in the course of a subsequent autopsy [1,2,5,8,12,16]. Scientific investigations have shown that in Germany at least half of the homicides remain unrevealed.…”
Section: Discussionmentioning
confidence: 94%
“…In this case, pathological findings and post-mortem imaging [ 11 , 12 ] suggested a mechanism of death (acute respiratory failure) coherent with a SIDS diagnosis, as it often features pulmonary findings. Petechial haemorrhages found sub-pleurally, sub-epicardially and in the thymus were also consistent with a SIDS [ 13 ].…”
Section: Discussionmentioning
confidence: 96%
“…Nevertheless, if the circumstances are lacking in plausible explanations [12], the occurrence of facial petechiae in newborns should be treated suspicious [28] and lead to thorough investigation [35]. Taken alone, caput succedaneum and facial petechiae cannot provide corroborative evidence of neonaticide and should therefore always be interpreted together with a further investigation of the circumstances of death and a thorough forensic pathological autopsy [36].…”
Section: Discussionmentioning
confidence: 99%